Presidents of War - Beschloss, Michael R. (New York : Crown, 2018)
Presidential historian Michael Beschloss uses original letters, diaries, declassified documents, and interviews to bring us into the room and into the minds of a procession of Chief Executives who took the nation into major conflicts, mobilized Americans for victory, and seized greater power for themselves. From James Madison and the War of 1812 to Lyndon Johnson and Vietnam, we see these leaders struggling with Congress, the courts, the press, their own advisers, and antiwar protesters; seeking comfort from their spouses, families, and friends; and dropping to their knees in prayer. We come to understand how these Presidents were able to withstand the pressures of war -- both physically and emotionally -- or were broken by them
Torrent of passion -- Man of straw -- The most glorious war -- The country is now virtually ours -- A presidential war -- Fort Sumter -- Blood flowing all about me -- Maine blown up -- We must keep what we want -- The world is on fire -- Salvation of mankind -- How could this thing happen? -- The survival war -- I am going to let them have it -- I didn't ask their permission -- We got slapped -- I don't have a parachute
Includes bibliographical references and index
Keywords: Presidents -- United States -- History; Political leadership -- United States -- History; Executive power -- United States -- History; Executive power; Political leadership; Presidents; United States -- History, Military; United States; Nonfiction; History; Military history